The difference of the concept of «diseas»" in the context of public health : (part 2 – experimental research) (Environment & Health, 2023)
Target. From the standpoint of public health, determine and analyze the ratio of various components of health disorders, namely biometric (disease), social (sickness), and its self-esteem (illness).Materials and methods. The source of the initial information was the survey data of the adult population. All questionnaire questions related to three manifestations of the health disorders: "disease", "illness", "sickness. Mathematical methods were used for the integral assessment of the components of health disorders, determination of the relationship between them and analysis of the obtained results.Results. For public health, which is the most socially oriented branch of medicine, it is extremely important to take into account not only biomedical (disease), but also social (sickness) aspects of the disease, as well as its self-esteem (illness). In this research, we considered the combination and relationship of various manifestations of the disease in Tweddle's triad, and conducted a comparative analysis of its components. It was established that the relationships between various forms of ill health depend on both the age and gender of the respondents. This must be considered, because knowledge of the ratio and relationship of the components of Tweddle's triad is necessary for the development of the most effective ways to overcome diseases and improve health. Considering the components of Tweddle's triad, namely, disease, illness and sickness, is extremely important for medicine, social policy and the health care system in general.
Keywords: public health; objective and subjective health; the concept of disease; morbidity of the population